2010
DOI: 10.1371/journal.pone.0010986
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of a Bacillus Isolate Causing Anthrax in Chimpanzees Combines Chromosomal Properties of B. cereus with B. anthracis Virulence Plasmids

Abstract: Anthrax is a fatal disease caused by strains of Bacillus anthracis. Members of this monophyletic species are non motile and are all characterized by the presence of four prophages and a nonsense mutation in the plcR regulator gene. Here we report the complete genome sequence of a Bacillus strain isolated from a chimpanzee that had died with clinical symptoms of anthrax. Unlike classic B. anthracis, this strain was motile and lacked the four prohages and the nonsense mutation. Four replicons were identified, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(190 citation statements)
references
References 85 publications
5
165
0
6
Order By: Relevance
“…Despite the multiple species names, which are often attributed to phenotypes conferred by mobile genetic elements, all these organisms can be considered members of a single species, because of their low genetic diversity, as measured by 16S sequencing (Daffonchio et al 2003) and multilocus sequence typing (MLST) (Priest et al 2004), and their high degree of shared gene content (Rasko et al 2005). Aside from B. anthracis, other reported virulent strains include a small number of nontraditional anthrax isolates (Hoffmaster et al 2004;Klee et al 2010), bacteria that cause wound or soft-tissue infections, a clonal complex of emetic toxin producers (Rasko et al 2007), and isolates responsible for food poisoning. Most B. cereus s.l.…”
mentioning
confidence: 99%
“…Despite the multiple species names, which are often attributed to phenotypes conferred by mobile genetic elements, all these organisms can be considered members of a single species, because of their low genetic diversity, as measured by 16S sequencing (Daffonchio et al 2003) and multilocus sequence typing (MLST) (Priest et al 2004), and their high degree of shared gene content (Rasko et al 2005). Aside from B. anthracis, other reported virulent strains include a small number of nontraditional anthrax isolates (Hoffmaster et al 2004;Klee et al 2010), bacteria that cause wound or soft-tissue infections, a clonal complex of emetic toxin producers (Rasko et al 2007), and isolates responsible for food poisoning. Most B. cereus s.l.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12] 2) Only two single-nucleotide differences appeared to be reliable markers for the specific identification of B. anthracis: a variant at nucleotide position 640 in the plcR gene or at position 1050 in the purA gene.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The main difference between these 672 Virulence Volume 4 Issue 8 species is the presence of unique virulence plasmids. However, data gathered in the last decade have shown that B. cereus strains that contain anthrax-specific pXO-like plasmids exist [7][8][9][10][11][12] which further obscures the much intermixed phylogenetic structure of the B. cereus group. Some PCR-based assays in use for detection of B. anthracis rely on plasmid-encoded targets in conjunction with a chromosomal marker to correctly differentiate pathogenic from apathogenic B. anthracis strains and B. anthracis from non-anthracis Bacillus species, respectively (for a review see ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Par exemple, une nouvelle bactérie du charbon Bacillus cereus biovar anthracis est létale pour les gorilles et les chimpanzés et a été trouvée au Cameroun, en Côte d'Ivoire et en République centrafricaine (Klee et al 2010) ; Pasteurella multocida et Streptococcus pneumoniae ont joué un rôle dans le foyer de maladie respiratoire chez les chimpanzés d'Afrique occidentale (Chi et al 2007 ;Köndgen et al 2008) ; des bactéries gastro-intestinales et des bactéries multi-résistantes, potentiellement dérivées de l'homme, ont été dépistées chez des grands singes vivant dans un habitat perturbé par l'homme (Nizeyi et al 2001 ;Rwego et al 2008) ; des souches pathogènes de Staphylococcus aureus ont été isolées chez des chimpanzés sauvages (Schaumburg et al 2012) tandis que Campylobacter jejuni associée à la diarrhée a été documentée chez les gorilles de montagne (Whittier et al 2010).…”
Section: Maladies Bactériennesunclassified